Mekanisme Pengurangan Masa Hukuman bagi Narapidana Korupsi di Lembaga Pemasyarakatan Kelas II A Bengkulu Dalam Fiqih Siyasah - Maman Wira Atmaja; Supardi; Qobli Khairi (Journal of Sharia and Legal Science, 2025)
With the issuance of the Regulation of the Minister of Law and Human Rights Number 07 of 2022 which fills the legal vacuum resulting from the judicial review of Government Regulation Number 99 of 2012 concerning the Second Amendment to Government Regulation Number 32 of 1999 concerning the Requirements and Procedures for the Implementation of the Rights of Correctional Inmates, it has become something that attracts attention. Because of course the mechanism for reducing the sentence thanks to the judicial review has changed. The main question of this study is whether information about the new sentence reduction mechanism has reached the prisoners. Meanwhile, it is generally known that the mechanism for reducing the sentence is not easy for prisoners to understand. Because in fact the reduction of the sentence is the right of all prisoners as regulated in the law. Thus, the purpose of this study is to determine how the mechanism for reducing the sentence in Class II A Bengkulu Prison works. This study is a qualitative study with an empirical legal approach. The results of the study show that the sentence reduction mechanism that applies according to the regulations is not effective in making prisoners get their rights, namely a reduction in sentence. In conclusion, the lack of understanding of prisoners regarding the mechanism for reducing the sentence creates a great potential that prisoners can fail to obtain their constitutional rights, namely a reduction in sentence.